Design and Development of a Website-Based Reservation Information System at the Backyard Villa - Ni Made Nadiya Aryadivani; I Wayan Ady Juliantara; I Made Agus Oka Gunawan (Yayasan Sraddha Panca Widya Nusantara, 2025)
The Backyard Villa is a medium-scale lodging business that relies on manual booking methods like text messages and phone calls. This approach leads to various issues, including delayed confirmations, data duplication or loss, and limited access to information for prospective guests. These inefficiencies negatively impact the operational effectiveness and overall service quality. This study aims to design and implement a web-based reservation information system to enhance service performance and competitiveness in the digital era. The system was developed using the waterfall method, which includes requirement analysis, system design, implementation, and testing phases. The system defines two main types of users—guests and admins with different access rights and features. System functionality testing was conducted on 28 scenarios, covering the booking process, villa data management, and reporting. The test results demonstrated a 100% success rate. The system not only simplifies the reservation process for customers through self-service but also supports the management in handling booking data, customer information, and operational reports more efficiently. The implementation of this system is expected to significantly improve the operational efficiency and service quality of The Backyard Villa by automating manual tasks, reducing errors, and providing a better user experience for both guests and management.